Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Beyond strength: dietary nitrate augments self-selected functional mobility after resistance training in middle-aged adults - Brandon M. Peoples; Mason C. McIntosh; Kenneth D. Harrison; Bria R. Smith; Keven G. Santamaria Guzman; Silvia E. Campos-Vargas; Damaris C. Cifuentes; Breanna J. Mueller; Andreas N. Kavazis; Darren T. Beck; Michael D. Roberts; Jaimie A. Roper (GeroScience, 2025)
This study aimed to assess whether dietary nitrate supplementation with resistance training (RT) augments gait performance and functional mobility in inactive middle-aged and older adults. We hypothesized that combining nitrate-rich beetroot juice (BRJ) with RT would yield improvements in gait and functional mobility compared to RT with nitrate-depleted beetroot juice placebo (PLA) supplementation. In this 12-week, randomized, double-blind, placebo-controlled pilot trial, 28 healthy, inactive adults (56 ± 7 years) were assigned to either a BRJ (~ 12.8 mmol nitrate/day) or PLA group while completing a supervised, full-body RT program (2×/week). Pre- and post-intervention assessments included the instrumented stand and walk (iSAW), 6-min walk test (i6MWT), and timed up and go (iTUG) tests. Supplement adherence, training compliance, and volume were equivalent between groups. ANCOVA analyses controlling baseline values revealed significant between-group differences favoring the BRJ group for gait speed (adjusted means: 1.38 vs 1.27 m/s, p = .010), stride length ( p < .001), and iTUG duration ( p < .05). Within-group analyses confirmed that the BRJ group experienced significant improvements in gait speed ( p < 0.001) and iTUG duration ( p < 0.05), while the PLA group showed no functional changes, indicating that 12 weeks of RT alone was insufficient to improve functional mobility in our sample despite equivalent training responses ( p > .05). In our middle-aged sample, supplementing dietary nitrate alongside RT led to clinically meaningful improvements in functional mobility during self-selected conditions, exceeding the gains from 12 weeks of twice-weekly RT alone. Preliminary descriptive analyses revealed sex-specific group-level differences that might suggest emerging trends. Although no inferential statistics were conducted, the patterns provide potential directions for future research investigating the effects of RT in middle-aged adults. Graphical Abstract

African mesquite elicits neuroprotective activity against quaternary metal mixture -induced olfactory bulb-hippocampal oxido-inflammatory stress via nrf2-hmox-1pathway - Orish E. Orisakwe; Evelyn Utomoibor Ikpeama; Chinna N. Orish; Anthonet N. Ezejiofor; Harrison Anezi Ozoani; Kenneth O. Okolo; Aleksandar Cirovic; Ana Cirovic; Ify L. Nwaogazie (Natural Product Research, 2025)

Verbal fluency dual-tasks show greater age-related cognitive-motor interference: a meta-analysis of walking performance - Kenneth Harrison; Keven Santa-Maria Guzman; Brandon M. Peoples; Silvia Campos-Vargas; Bria R. Smith; Damaris C. Cifuentes; Grace Greer; Kristina A. Neely; Jaimie A. Roper (Experimental Brain Research, 2025)
A substantial body of literature has examined gait during cognitive dual-tasking in younger and older adults. However, it remains unclear how, and to what extent, different cognitive tasks uniquely influence gait. This meta-analysis quantified age-related differences in gait speed during dual-task walking. Importantly, we examined cognitive task as a potential moderator. We searched Web of Science for studies comparing young and older adults during single-task and dual-task walking conditions. Twenty-two studies met the inclusion criteria, representing 544 young adults (mean age range: 20–31 years) and 511 older adults (mean age range: 62–85 years). Studies employed primarily serial subtraction tasks (n = 12) and verbal fluency tasks (n = 8); however, one study used digit vigilance, and another used a texting paradigm during walking. Random-effects meta-analysis using standardized mean differences (Hedges' g) revealed a significant overall effect (g = −0.2612, 95% CI [−0.4914, –0.0310], p = 0.0261), indicating greater dual-task costs in older adults compared to younger adults with a small to medium effect size. Substantial heterogeneity was observed across studies (I 2 = 66.53%, p < 0.0001). Subgroup analysis demonstrated that verbal fluency tasks produced a larger and statistically significant age-related difference (g = −0.4744, 95% CI [−0.8712, −0.0777], p = 0.0191), while serial subtraction tasks showed smaller, non-significant effects (g = −0.1412, p = 0.3474). These findings suggest that verbal fluency creates unique neural resource competition in older adults, involving prefrontal, cerebellar, and basal ganglia circuits that support both language production and gait control. The task-specific vulnerability to verbal fluency, and not serial subtraction, provides evidence for age-related changes in cognitive-motor integration. Rehabilitation strategies targeting executive functions may be effective for maintaining mobility in aging populations.

Isotopic evidence from a Brazos River (Texas, USA) Cretaceous/Paleogene boundary section consistent with a pulse of greenhouse warming shortly after the Chicxulub impact - Kenneth G. MacLeod; Brian T. Huber; Clay Tabor; Siddhartha Mitra; Rachel Wheatley; Cheryl Harrison; Maya Tessler; Charles Bardeen; Nicole S. Lovenduski; Julio Sepúlveda; Joshua Coupe; Shixiong Hu (Global and Planetary Change, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Benthic community heterogeneity on the Eastern Antarctic continental shelf - Candace J. Grimes; Andrew R. Mahon; Kyle B. Donnelly; William Farris; Madison Gott; Coral Halanych; Conor Judge; Harrison I. Mancke; Nusrat J. Noor; Samantha A. Schreiter; Lindsay Uzarski; Jessica R. Zehnpfennig; et al. (Polar Biology, 2025)

Gait Velocity Alterations in Essential Tremor: a Meta-Analysis - Kenneth Harrison; Brandon M. Peoples; Keven G. Santamaria Guzman; Emily J. Hunter; Harrison C. Walker; Jaimie A. Roper (The Cerebellum, 2024)
Essential tremor (ET) is a prevalent movement disorder that impairs gait function, including gait speed - a critical marker of mobility disability and adverse outcomes. This meta-analysis aimed to quantify differences in gait speed between individuals diagnosed with ET compared to people without a movement disorder diagnosis. Electronic databases were searched for studies comparing gait speed in ET patients and controls. Effect sizes were calculated using standardized mean differences (Hedges’ g) and pooled using a random-effects model. Eight studies (390 ET, 227 controls) were included. ET patients exhibited significantly slower gait speeds than controls. The effect size (Hedges’ g = -1.06, 95% CI -1.47 to -0.65, p < .001) indicates a large, clinically significant difference. Substantial study heterogeneity was observed (I 2 = 76.9%). These findings suggest that gait speed deficits are a significant feature of ET, potentially reflecting cerebellar dysfunction. This highlights the need for gait assessment and targeted interventions in ET management to reduce fall risk and improve quality of life. Understanding the moderating factors such as medication type and state, disorder severity, and age could provide significant benefits in the treatment and management of ET.

Humpback whales (Megaptera novaeangliae) in Hervey Bay, Australia: a stopover for females early in their southern migration - Lyndon Brooks; Trish Franklin; Wally Franklin; Peter Harrison; Peter Corkeron; Kenneth H. Pollock (Frontiers in Marine Science, 2024)
In the Southern Hemisphere, humpback whales ( Megaptera novaeangliae ) migrate along the extended continental coastlines of Australia, South America, and South Africa. This study reports on photo-identification capture–recapture data from a long-term survey conducted in Hervey Bay, Queensland, where a substantial proportion of the population stop over early in the southern migration. Photo-identification data were collected over 10 weeks per year from 1997 to 2009. The migration through Hervey Bay is dominated and led by females with high fidelity to the site. Mature females, yearlings, and immature whales use the Bay during August, while mature lactating females with calves dominate during September and October. Complex social behaviours occur throughout the season and differ between the early and late cohorts. We argue that the composition of the two cohorts and their distinctively different behaviours indicate that Hervey Bay is not simply a resting site but an area of aggregation that serves important social and biological benefits. A multistate open robust design model was fitted to capture–recapture data to estimate the annual number of whales visiting the Bay, the permanent emigration rate, proportions of the visiting population that do not enter the Bay each year, the number present during each week, and their residency times. The number of annual visitors to the Bay increased approximately linearly from 857 in 1997 to 2175 at the end of sampling in 2009 with two-thirds migrating through during the first half of each season. The population rate of growth may have been slowing by 2009, but there was considerable uncertainty in the trajectory and little basis for projection into the future. While it is desirable to know the current status of the Hervey Bay population and what has occurred since 2009, the cost and effort required make further manual collection and matching of images unlikely. The development of AI algorithmic matching software may enable further research in future.

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Ameliorative Effects of Zn and Se Supplementation on Heavy Metal Mixture Burden via Increased Renal Metal Excretion and Restoration of Redoxo-Inflammatory Alterations - Harrison Ozoani; Anthonet N. Ezejiofor; Kenneth O. Okolo; Chinna N. Orish; Ana Cirovic; Aleksandar Cirovic; Orish E. Orisakwe (Biological Trace Element Research, 2024)

Is the Coral Triangle’s future shown in a Pliocene reef gap? - G. William M. Harrison; Nadia Santodomingo; Kenneth G. Johnson; Willem Renema (Coral Reefs, 2023)
Although Pliocene temperature and pCO2 are similar to those predicted in the IPPC RCP4.5 scenario, the distribution of coral reefs in the center of maximum coral diversity, the Coral Triangle, during this period has not been explored. We discovered a significantly lower occurrence of reefs during the Pliocene, which we refer to as the Pliocene Reef Gap, but this decrease was not associated with a drop in coral genus richness. While some of the multiple local causes that drove this decline, such as sea level rise, are analogs to drivers of Anthropocene reef decline, neither warming nor increasing pCO2 are among them.

Life-history guilds of fishes associated with estuaries: opportunism versus dependency - Alan K. Whitfield; Kenneth W. Able; Mario Barletta; Stephen J.M. Blaber; Trevor D. Harrison (Estuarine, Coastal and Shelf Science, 2023)

Ginkgo biloba supplement abates lead-induced endothelial and testicular dysfunction in Wistar rats via up-regulation of Bcl-2 protein expression, pituitary-testicular hormones and down-regulation of oxido-inflammatory reactions - Jerome Ndudi Asiwe; Enekabokom Nwoke Ekene; Linda Chinyere Agbugba; Emuesiri Goodies Moke; Abimbola Victoria Akintade; Benneth Ben-Azu; Harrison Eruotor; Tarela Melish Elias Daubry; Kenneth Kelechi Anachuna; Mega O. Oyovwi (Journal of Trace Elements in Medicine and Biology, 2023)

Zinc and selenium attenuate quaternary heavy metal mixture-induced testicular damage via amplification of the antioxidant system, reduction in metal accumulation, inflammatory and apoptotic biomarkers - Harrison Ozoani; Anthonet N. Ezejiofor; Kenneth O. Okolo; Chinna N. Orish; Ana Cirovic; Aleksandar Cirovic; Orish E. Orisakwe (Toxicological Research, 2023)

Quantifying spatial extents of artificial versus natural reefs in the seascape - D’amy N. Steward; Avery B. Paxton; Nathan M. Bacheler; Christina M. Schobernd; Keith Mille; Jeffrey Renchen; Zach Harrison; Jordan Byrum; Robert Martore; Cameron Brinton; Kenneth L. Riley; J. Christopher Taylor; et al. (Frontiers in Marine Science, 2022)
With increasing human uses of the ocean, existing seascapes containing natural habitats, such as biogenic reefs or plant-dominated systems, are supplemented by novel, human-made habitats ranging from artificial reefs to energy extraction infrastructure and shoreline installments. Despite the mixture of natural and artificial habitats across seascapes, the distribution and extent of these two types of structured habitats are not well understood but are necessary pieces of information for ocean planning and resource management decisions. Through a case study, we quantified the amount of seafloor in the southeastern US (SEUS; 103,220 km 2 in the Atlantic Ocean; 10 – 200 m depth) covered by artificial reefs and natural reefs. We developed multiple data-driven approaches to quantify the extent of artificial reefs within state-managed artificial reef programs, and then drew from seafloor maps and published geological and predictive seafloor habitat models to develop three estimates of natural reef extent. Comparisons of the extent of natural and artificial reefs revealed that artificial reefs account for substantially less habitat (average of two estimates 3 km 2 ; <0.01% of SEUS) in the region than natural reefs (average of three estimates 2,654 km 2 ; 2.57% of SEUS) and that this pattern holds across finer regional groupings (e.g., states, depth bins). Our overall estimates suggest that artificial reef coverage is several orders of magnitude less than natural reef coverage. While expansive seafloor mapping and characterization efforts are still needed in SEUS waters, our results fill information gaps regarding the extent of artificial and natural reef habitats in the region, providing support for ecosystem-based management, and demonstrating an approach applicable to other regions.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Development of duplex qPCR targeting Carnobacterium maltaromaticum and Vagococcus salmoninarum - Isaac Standish; Rebekah McCann; Corey Puzach; Eric Leis; Jennifer Bailey; Sara Dziki; Ryan Katona; Ellen Lark; Carey Edwards; Brandon Keesler; Stephen Reichley; Stacy King; et al. (Journal of Fish Diseases, 2022)
In November 2018, Vagococcus salmoninarum was identified as the causative agent of a chronic coldwater streptococcosis epizootic in broodstock brook trout ( Salvelinus fontinalis ) at the Iron River National Fish Hatchery in Wisconsin, USA. By February 2019, the epizootic spread to adjacent raceways containing broodstock lake trout ( Salvelinus namaycush ), whereby fish were found to be coinfected with Carnobacterium maltaromaticum and V . salmoninarum . To differentiate these two pathogens and determine the primary cause of the lake trout morbidity, a quantitative real‐time PCR (qPCR) was developed targeting the C . maltaromaticum phenylalanyl‐tRNA synthase alpha subunit ( pheS ) gene. The qPCR was combined with a V . salmoninarum qPCR, creating a duplex qPCR assay that simultaneously quantitates C. maltaromaticum and V . salmoninarum concentrations in individual lake trout tissues, and screens presumptive isolates from hatchery inspections and wild fish from national fish hatchery source waters throughout the Great Lakes basin. Vagococcus salmoninarum and C. maltaromaticum were co‐detected in broodstock brook trout from two tribal hatcheries and C. maltaromaticum was present in wild fish in source waters of several national fish hatcheries. This study provides a powerful new tool to differentiate and diagnose two emerging Gram‐positive bacterial pathogens.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

A philosophical basis for hydrological uncertainty - Grey S. Nearing; Yudong Tian; Hoshin V. Gupta; Martyn P. Clark; Kenneth W. Harrison; Steven V. Weijs (Hydrological Sciences Journal, 2016)

Bayesian approach to contaminant source characterization in water distribution systems: adaptive sampling framework - Hui Wang; Kenneth W. Harrison (Stochastic Environmental Research and Risk Assessment, 2013)

Isolation and characterization of 18 novel polymorphic microsatellite markers from the Mayan cichlid (Cichlasoma urophthalmus) - Elizabeth Harrison; Cara N. Love; Kenneth L. Jones; Stacey L. Lance; Joel C. Trexler; Timothy Collins (Conservation Genetics Resources, 2013)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Potential effects of climate change on DOC release from three different soil types on the Northern Pennines UK: examination using field manipulation experiments - ANTHONY F. HARRISON; KENNETH TAYLOR; ANDY SCOTT; JAN POSKITT; DAVID BENHAM; JOHN GRACE; JACKY CHAPLOW; PHILIP ROWLAND (Global Change Biology, 2008)
Three field manipulation experiments were carried out during 1993–1995 on the Northern Pennines to investigate the influences of temperature, solar radiation and rainfall on the release of dissolved organic carbon (DOC) from vegetated soil cores using zero‐tension lysimeters. The cores were manipulated by being translocated to four sites down a climatic gradient, by artificial soil heating or being exposed to double normal rainfall. In each experiment three soil types, a brown earth, a micropodzol and a peaty gley, with differing organic matter content and distribution within the profile, were studied. DOC data, expressed as mg C m −2 day −1 , were analysed following log 10 transformation, by a repeated measures analysis of variance procedure, using climatic variables measured concurrently with sampling, and 1 and 2 months before sampling. DOC release was dominated by rainfall but was also associated with solar radiation and temperature. With each of the three climatic variables, rainfall, solar radiation and temperature, both positive and negative effects on DOC release have been found significant, indicating that the concurrent and delayed effects of the same variable may be different. DOC release was positively related with all three soils to concurrent rainfall, indicating rainfall's primary leaching action. DOC release was also negatively related to rainfall of the previous month indicating that its action depletes the leachable pool of DOC in the soil. DOC release was positively associated with solar radiation 2 months earlier, indicating that DOC's main source is that of primary production; DOC peaks closely followed peaks of annual primary production. DOC release was linked with temperature, the strongest association being with temperature 2 months earlier, indicating that temperature effects both primary production and DOC regeneration via organic matter decomposition. A conceptual model, relating our findings to those processes known to govern DOC release from soils, has been presented.

Phylogeography of spruce beetles ( Dendroctonus rufipennis Kirby) (Curculionidae: Scolytinae) in North America - LUANA S. MAROJA; STEVEN M. BOGDANOWICZ; KIMBERLY F. WALLIN; KENNETH F. RAFFA; RICHARD G. HARRISON (Molecular Ecology, 2007)
Tree‐feeding insects that are widespread in north temperate regions are excellent models for studying how past glaciations have impacted differentiation and speciation. We used mitochondrial DNA (mtDNA) sequences and allele frequencies at nine microsatellite loci to examine genetic population structure across the current range of the spruce beetle ( Dendroctonus rufipennis ), an economically important insect in North America. Two major haplotype groups occur across northern North America, from Newfoundland to Alaska, on white spruce ( Picea glauca ), and a third distinctive haplotype group occurs throughout the Rocky Mountains on Engelmann spruce ( Picea engelmannii ). The two mtDNA lineages found in northern populations are 3–4% divergent from each other and from the lineages found in the Rocky Mountains. Analyses of microsatellite data also suggest the existence of major population groupings associated with different geographical regions. In the Pacific Northwest, concordant contact zones for genetically distinct populations of spruce beetles and their principal hosts appear to reflect recent secondary contact. Although we could detect no evidence of historical mtDNA gene flow between allopatric population groups, patterns of variation in the Pacific Northwest suggest recent hybridization and introgression. Together with the pollen record for spruce, they also suggest that beetles have spread from at least three glacial refugia. A minimum estimate of divergence time between the Rocky Mountain and northern populations was 1.7 Myr (million years), presumably reflecting the combined effects of isolation during multiple glacial cycles.

A closer look at detectability - Fred L. Ramsey; Kenneth Harrison (Environmental and Ecological Statistics, 2004)

Detection and Quantification of Spongospora subterranea f. sp. subterranea in Soils and on Tubers Using Specific PCR Primers - Kenneth S. Bell; Jane Roberts; Susan Verrall; Daniel W. Cullen; Naomi A. Williams; Julian G. Harrison; Ian K. Toth; David E.L. Cooke; James M. Duncan; Jamie R. Claxton (European Journal of Plant Pathology, 1999)

Effects of climate change on nitrogen dynamics in upland soils. 2. A soil warming study - Philip Ineson; David G. Benham; Janet Poskitt; Anthony F. Harrison; Kenneth Taylor; Clive Woods (Global Change Biology, 1998)
A new warming technique has been developed in a field experimental study of the potential effects of climatic change on N leaching from hill land plant/soil systems. Thermocouple compensating cable has been utilized to provide a small cross‐section, flexible, low voltage heating cable, mounted on a framework of stainless steel mesh, to provide uniform heating at the vegetation/soil interface of zero‐tension lysimeters and surrounding turf. We describe a specially designed heat controller capable of maintaining a temperature differential of 3 °C above ambient at a soil depth of 0.8 cm. The equipment raises temperatures down the soil profile and within the grass sward, whilst tracking normal diurnal temperature variation. Results presented here illustrate the efficacy of the warming technique, together with the consequences for the release of nitrate from lysimeters. The responses of soil solution concentrations of nitrate varied markedly between soil types, but showed a significant decrease in the brown earth during the first 5 months of additional heating. This suggests that increased nutrient release is masked by plant uptake in this soil, but the responses in the other two soils were less marked.

Effects of climate change on nitrogen dynamics in upland soils. 1. A transplant approach - Philip Ineson; Kenneth Taylor; Anthony F. Harrison; Janet Poskitt; David G. Benham; Edward Tipping; Colin Woof (Global Change Biology, 1998)
The impact of climate change on N leaching from hill land plant/soil systems was investigated using a transplant technique involving the movement of intact lysimeter cores of three contrasting soil types down an altitudinal gradient at Great Dun Fell, Cumbria. Air and soil temperatures and precipitation were monitored at four elevations down an altitudinal transect using automatic weather stations for a period of two years. The altitudinal sequence of air temperature followed the anticipated pattern, providing mean annual temperatures at the four locations of 3.4, 5.0, 6.3 and 8.1 °C. Lapse rates of both mean air and soil temperatures over the altitudinal range 171–845 m were 6.6 (1993) and 7.0 °C km –1 (1994). Soil monthly temperature gradients for a particular soil type for each of the two years showed a seasonal range of 6.0 and 7.4 °C km –1 , respectively, and for air temperature of 4.3 and 3.1 °C km –1 . Precipitation gradients showed the expected general increase with altitude, but were less predictable. Inorganic nitrogen leaching was studied in lysimeter leachates with climatic amelioration resulting in dramatic reductions in leachate nitrate concentrations and associated total concentrations of inorganic nitrogen. Decreases in leachate nitrate concentrations were observed for all three soil types studied. Soils receiving supplemented rainfall also showed decreased N concentrations, suggesting that temperature was the main controlling factor responsible for the observed reductions. Increased N uptake by the vegetation, in response to the increases in temperature, is considered to be critical in controlling soil solution chemistry at these sites.